Unveiling the Dark Side of Workplace Connectivity: A Qualitative Meta-Synthesis of Digital Presenteeism, Employee Well-Being, and Sustainable Performance - Nurhaeda Zaeni; M. Maryadi; Abd. Rajab (Golden Ratio of Mapping Idea and Literature Format, 2026)
Digital communication technologies have transformed workplace operations by increasing flexibility, efficiency, and collaboration. However, they also contribute to digital presenteeism, where employees remain digitally available and responsive despite fatigue, illness, psychological distress, or being outside working hours. This systematic literature review uses a qualitative meta-synthesis approach to examine the relationship between digital presenteeism, employee well-being, and sustainable performance. Based on 139 peer-reviewed articles from Scopus, Web of Science, ScienceDirect, and Emerald Insight, the review identifies key themes such as always-on work culture, blurred work-life boundaries, technostress, hidden labor, productivity paradox, declining well-being, and sustainable performance challenges. The findings show that excessive digital connectivity and constant availability expectations increase techno-overload, emotional exhaustion, work-life imbalance, and burnout. Although digital presenteeism may create short-term productivity, it can weaken long-term employee well-being and organizational sustainability. This study proposes a conceptual framework highlighting the role of organizational support, digital leadership, right-to-disconnect policies, and boundary management practices in reducing the negative effects of digital presenteeism.